Evolving Roles of Natural Terpenoids From Traditional Chinese Medicine in the Treatment of Osteoporosis - Zhuo, Yue; Li, Meng; Jiang, Qiyao; Ke, Hanzhong; Liang, Qingchun; Zeng, Ling-Feng; Fang, Jiansong (Frontiers in Endocrinology, 2022)
Osteoporosis (OP) is a systemic metabolic skeletal disease which can lead to reduction in bone mass and increased risk of bone fracture due to the microstructural degradation. Traditional Chinese medicine (TCM) has been applied in the prevention and treatment of osteoporosis for a long time. Terpenoids, a class of natural products that are rich in TCM, have been widely studied for their therapeutic efficacy on bone resorption, osteogenesis, and concomitant inflammation. Terpenoids can be classified in four categories by structures, monoterpenoids, sesquiterpenoids, diterpenoids, and triterpenoids. In this review, we comprehensively summarize all the currently known TCM-derived terpenoids in the treatment of OP. In addition, we discuss the possible mechanistic-of-actions of all four category terpenoids in anti-OP and assess their therapeutic potential for OP treatment.